The Pedagogical Relevance of the Deep Learning Approach to the Formation of the Eight Dimensions of Graduate Profiles in Elementary School Learning - Mega Setya Handayani; Mawaddah Warohmah; Mochammad Achwan Baharudin; Ibrahim Pandu Ame (Program Studi PGSD, Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2025)
This research is prompted by the low literacy, numeracy, and science skills of Indonesian students, as indicated by 2022 PISA scores, which suggest a dominance of Lower Order Thinking Skills (LOTS). As a strategic solution, the Ministry of Elementary and Secondary Education (Kemendikdasmen) introduced the Deep Learning approach in 2025 as a new paradigm to enhance educational quality. This study aims to explore the fundamental concepts of Deep Learning in elementary education and analyze its pedagogical relevance to the eight dimensions of the graduate profile. Using a library research method, analyzing 27 recent literature sources, the findings show that Deep Learning, anchored on the pillars of Mindful, Meaningful, and Joyful, is highly relevant in holistically integrating cognitive, affective, and spiritual domains. This approach successfully shifts learning orientation from mere content completion to the development of profound learning experiences. The study confirms that Deep Learning serves as a strategic operational mechanism for producing intelligent, character-driven graduates. The study recommends that educators reorient their roles as learning experience designers and calls for technical policy support to facilitate reflective classroom practices, bridging the gap between conceptual understanding and actual implementation in elementary schools.